Challenges in Learning Japanese Language in Riau: A Comprehensive Analysis - Nana Rahayu; L.N. Firdaus; Hadriana Hadriana; Sumarno Sumarno (STAI Hubbulwathan Duri, 2023)
The Japanese high school curriculum is the same in Riau as in other regions; it is part of the specialty. Consequently, learning Japanese will take much less time. It is challenging for Japanese language teachers to meet learning objectives because of the required minimum hours of instruction. Therefore, this study aimed to outline the challenges Japanese high school teachers in Riau had when trying to learn Japanese. 36 Japanese instructors in Riau were polled for this study. Japanese language teachers and other issues like infrastructure and facilities present difficulties for students learning the language. According to this survey, high school students who struggled to read Hiragana faced the five most common forms of challenges learning Japanese: (1) Students who had difficulty reading Hiragana and Katakana, (2) Students who had a problem writing Hiragana and Katakana, (3) Students who had trouble pronouncing Japanese words correctly, (4) Some teachers still used traditional teaching methods, and (5) Students had little interest in speaking Japanese. The findings showed that the process of boosting students' motivation to talk to Japanese presented the most challenge. The majority of the 22 (61.1%) Japanese high school instructors in Riau concurred that the cause of the students was still low. Of course, this may be avoided by encouraging instructors to be more inventive when creating relevant teaching materials, engaging learning media, and putting the needs of the students first.